Effects of guanethidine-induced sympathectomy on the spermatogenic and steroidogenic testicular functions of prepubertal to mature rats - Carvalho, TLL; Guimaraes, M. A.; Kempinas, W. G.; Petenusci, S. O.; Silva, AAMR (Blackwell Wissenschafts Verlag Gmbh, 1996)
Selective chemical sympathectomy of the internal genital organs of prepubertal to mature male Wistar rats was performed by chronic treatment with low doses of guanethidine. Sympathetic denervation caused an increase in intratesticular progesterone levels in prepubertal and early pubertal rats in addition to a decrease in androstenedione and testosterone levels in prepubertal animals, thus indicating a decrease in the conversion of progesterone into androgen, probably by blocking the steroidogenic enzymatic pathway at the 17 alpha-hydroxylase/17,20 desmolase level. A lower degree of testicular maturation, probably related to reduced androgen activity, was observed in prepubertal and early pubertal sympathectomized rats. Concentration of spermatozoa, on the other hand, was increased in the enlarged cauda epididymidis of late pubertal and mature denervated animals. This result is discussed in terms of the impairment of epididymal mechanisms of seminal emission, fluid resorption and spermatozoal disposal.
Keywords: steroidogenesis; spermatogenesis; sperm; sympathectomy; rat